Hysteretic properties and numerical simulation of new self-centering coupling beams - Jizhi SU; Zhenyu TONG; Yong LI; Haifeng YU; Haoxuan ZHANG; Zuanfeng PAN (Journal of Hebei University of Science and Technology)
Aiming at the problem that the damaged parts in replaceable beam cannot be disassembled and replaced due to excessive residual displacement after strong earthquakes, a new self-centering coupling beams (SCCB) based on shape memory alloy (SMA) rod was proposed. Firstly, a new self-centering friction damper was designed and tested to study its mechanical properties. Secondly, the low cycle reciprocating loading test was carried out on the same SCCB specimen to explore the effect of loading rate on its hysteresis performance. Finally, a finite element model of SCCB was established and parameterized. The results show that the hysteretic properties of SCCB show a typical "flag type" . When the friction force is 10 kN, the loading rate increases from 1 mm/min to 10 mm/min, and the hysteretic area decreases by 34.45%; Increasing the diameter of SMA rod can improve the stiffness, bearing capacity and energy consumption of SCCB, and reduce the residual displacement; Increasing the pretension of SMA rod can improve the stiffness and bearing capacity, which has little influence on energy consumption. SCCB can effectively improve the adaptability of structures to residual displacement after strong earthquakes, providing reference for the design of replaceable beams.